2014
DOI: 10.1016/b978-0-12-800977-2.00007-3
|View full text |Cite
|
Sign up to set email alerts
|

The Intergenerational Effects of Early Adversity

Abstract: Early insults during critical periods of brain development, both prenatal and postnatal, can result in epigenetic changes that may impact health and behavioral outcomes over the life span and into future generations. There is ample evidence that these early stages of brain development are sensitive to various environmental insults, including malnutrition, childhood trauma, and drug exposures. The notion that such changes, both physiological and behavioral, can also carry over into subsequent generations has lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 118 publications
0
21
0
1
Order By: Relevance
“…These studies, and others not included here, support gene x childhood maltreatment interactions, including epigenetic modifications, in risk for, and illness course in, mood disorders. Epigenetics may also be one mechanism that contributes to the intergenerational transmission of trauma, as previously discussed [131][132][133]. Although it is important to note that non-genomic mechanisms are also implicated in the intergenerational transmission of behavior [134].…”
Section: Underlying Mechanisms By Which Childhood Maltreatment Increamentioning
confidence: 89%
“…These studies, and others not included here, support gene x childhood maltreatment interactions, including epigenetic modifications, in risk for, and illness course in, mood disorders. Epigenetics may also be one mechanism that contributes to the intergenerational transmission of trauma, as previously discussed [131][132][133]. Although it is important to note that non-genomic mechanisms are also implicated in the intergenerational transmission of behavior [134].…”
Section: Underlying Mechanisms By Which Childhood Maltreatment Increamentioning
confidence: 89%
“…Protein restriction during development interferes with the neocortical morpho-functional and sub-cortical synaptic organization and affects the biochemical, behavioral, and electrophysiological consequences of individual, thus limiting cognitive abilities and other behavioral patterns. The resulting altered fetal programming impairs the physiology, organ development, function, maturation, hormonal profile, and pre-disposition to metabolic, mental and cognitive disorders in rats (Levay et al, 2010 ; Del Arco et al, 2011 ; Zhang et al, 2012 ; Marques et al, 2014 ) and human (Kar et al, 2008 ; Waber et al, 2014 ; Georgieff, 2015 ; reviewed by Galler and Rabinowitz, 2014 ) Despite extensive literature evidencing the detrimental effects of maternal protein malnutrition on behavioral and cognitive deficits in animal models, most of the studies have followed short restriction protocols either modeling the gestational or early gestational malnutrition along with lactational periods (Glover, 2011 ; Sandman et al, 2011 ; Alamy and Bengelloun, 2012 ; Kerac et al, 2014 ). Such short protocols of protein restriction don't completely emulate the clinical conditions of females in developing and underdeveloped countries.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in rodents have established the consequences of malnutrition on brain development and behavior (Zhang et al, 2010 ; Reyes-Castro et al, 2012 ). Prenatal stress like maternal diet inadequacy, pollutants, toxicants, and distress have been reported to significantly affect the neuro-cognitive development (Bale et al, 2010 ; Glover, 2011 ; Sandman et al, 2011 ; Huang et al, 2013 ; Galler and Rabinowitz, 2014 ; Marques et al, 2014 ; Waber et al, 2014 ). Clinical studies have evidenced that undernourishment induced alterations are associated with delays in motor and cognitive functions like decreased IQ scores, impaired learning and memory, reduced social skills, and impaired school performance (Berkman et al, 2002 ; Kar et al, 2008 ; Hemb et al, 2010 ; Ghazi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early institutionalization or being raised in an orphanage, as deprivation-related adversities, resulted in developmental delays in social, behavioral and cognitive domains ( Chugani et al, 2001 ; Johnson et al, 2006 ). Some studies have even suggested that such effects may be intergenerational ( Galler and Rabinowitz, 2014 ). The long-lasting temporal influence of behavioral experience has invoked a variety of mechanistic explanations, most notably epigenetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%